IMPLEMENTASI STRATEGI PEMBELAJARAN EDUPRENEURSHIP BERBASIS MULTIPLE INTELLIGENCES - Asrul Faruq; M. Sofyan Alnashr (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2017)
This written to make an explain edupreneurship who are given by education institution –included is college– to him educate participant so that entrepreneur mental educate participant have growing up. The hopes edupreneurship can shaping creative character and independent from educate participant. Range from to selection learning strategy who are exact and agree with child learning style. So that multiple intelligences theory from Howard Gardner can be phenomenological in the edupreneurship strategy application. Edupreneurship strategy based multiple intelligences to do with educate participant activity used with one of intelligences or some intellegences collaboration in the edupreneurship learning.